Liberal Feminism In The Little Women Movie - Risna Sofia; Bima Prana Chitra; Misla Geubrina (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The research objectives are (1) To find out the kinds of gender discrimination experienced by Jo March in the Little Women movie, and (2) To analyze how Jo March represents liberal feminism in the little women movie. The writer uses the dynamic structuralism theory by Mukarovsky. In conducting the study, the writer uses library research. The data in this study were taken from quotations such as dialogues, sentences and phrases in the movie script of Little Women as source of data. The results of the study showed that there are kinds of gender discrimination that occur in Little Women movie are discrimination in society, discrimination in education, discrimination in employement, discrimination in politics and depicting liberal feminism by facing the stereotype of women, she rejects the stereotype by proving that she can live well without marrying a rich man.